The Role of Nutrition in Maintaining Health in the Nation's Elderly: Evaluating Coverage of Nutrition Services for the Medicare Population - Institute of Medicine (The National Academies Press, 2000)
Malnutrition and obesity are both common among Americans over age 65. There are also a host of other medical conditions from which older people and other Medicare beneficiaries suffer that could be improved with appropriate nutritional intervention. Despite that, access to a nutrition professional is very limited. Do nutrition services benefit older people in terms of morbidity, mortality, or quality of life? Which health professionals are best qualified to provide such services? What would be the cost to Medicare of such services? Would the cost be offset by reduced illness in this population? This book addresses these questions, provides recommendations for nutrition services for the elderly, and considers how the coverage policy should be approached and practiced. The book discusses the role of nutrition therapy in the management of a number of diseases. It also examines what the elderly receive in the way of nutrition services along the continuum of care settings and addresses the areas of expertise needed by health professionals to provide appropriate nutrition services and therapy.

Extending Medicare Coverage for Preventive and Other Services - Institute of Medicine (The National Academies Press, 2000)
This report, which was developed by an expert committee of the Institute of Medicine, reviews the first three services listed above. It is intended to assist policymakers by providing syntheses of the best evidence available about the effectiveness of these services and by estimating the cost to Medicare of covering them. For each service or condition examined, the committee commissioned a review of the scientific literature that was presented and discussed at a public workshop. As requested by Congress, this report includes explicit estimates only of costs to Medicare, not costs to beneficiaries, their families, or others. It also does not include cost-effectiveness analyses. That is, the extent of the benefits relative to the costs to Medicare2014or to society generally2014is not evaluated for the services examined. The method for estimating Medicare costs follows the generic estimation practices of the Congressional Budget Office (CBO). The objective was to provide Congress with estimates that were based on familiar procedures and could be compared readily with earlier and later CBO estimates. For each condition or service, the estimates are intended to suggest the order of magnitude of the costs to Medicare of extending coverage, but the estimates could be considerably higher or lower than what Medicare might actually spend were coverage policies changed. The estimates cover the five-year period 2000-2004. In addition to the conclusions about specific coverage issues, the report examines some broader concerns about the processes for making coverage decisions and about the research and organizational infrastructure for these decisions. It also briefly examines the limits of coverage as a means of improving health services and outcomes and the limits of evidence as a means of resolving policy and ethical questions.

Ending Neglect: The Elimination of Tuberculosis in the United States - Institute of Medicine (The National Academies Press, 2000)
Tuberculosis emerged as an epidemic in the 1600s, began to decline as sanitation improved in the 19th century, and retreated further when effective therapy was developed in the 1950s. TB was virtually forgotten until a recent resurgence in the U.S. and around the world2014ominously, in forms resistant to commonly used medicines. What must the nation do to eliminate TB? The distinguished committee from the Institute of Medicine offers recommendations in the key areas of epidemiology and prevention, diagnosis and treatment, funding and organization of public initiatives, and the U.S. role worldwide. The panel also focuses on how to mobilize policy makers and the public to effective action. The book provides important background on the pathology of tuberculosis, its history and status in the U.S., and the public and private response. The committee explains how the U.S. can act with both self-interest and humanitarianism in addressing the worldwide incidence of TB.

Rational Therapeutics for Infants and Children: Workshop Summary - Institute of Medicine (The National Academies Press, 2000)
The Institute of Medicine's (IOM's) Roundtable on Research and Development of Drugs, Biologics, and Medical Devices evolved from the Forum on Drug Development, which was established in 1986. Sponsor representatives and IOM determined the importance of maintaining a neutral setting for discussions regarding long-term and politically sensitive issues justified the need to revise and enhance past efforts. The new Roundtable is intended to be a mechanism by which a broad group of experts from the public* and private sectors can be convened to conduct a dialogue and exchange information related to the development of drugs, biologics, and medical devices. Members have expertise in clinical medicine, pediatrics, clinical pharmacology, health policy, health insurance, industrial management, and product development; and they represent interests that address all facets of public policy issues. From time to time, the Roundtable requests that a workshop be conducted for the purpose of exploring a specific topic in detail and obtaining the views of additional experts. The first workshop for the Roundtable was held on April 14 and 15, 1998, and was entitled Assuring Data Quality and Validity in Clinical Trials for Regulatory Decision Making. The summary on that workshop is available from IOM. This workshop summary covers the second workshop, which was held on May 24 and 25, 1999, and which was aimed at facilitating the development and proper use of drugs, biologics, and medical devices for infants and children. It explores the scientific underpinnings and clinical needs, as well as the regulatory, legal, and ethical issues, raised by this area of research and development.

Developing Technologies for Early Detection of Breast Cancer: A Public Workshop Summary - Institute of Medicine; National Research Council
In November 1999, the Institute of Medicine, in consultation with the Commission on Life Sciences, the Commission on Physical Sciences, Mathematics, and Applications, and the Board on Science, Technology and Economic Policy launched a one year study on technologies for early detection of breast cancer. The committee was asked to examine technologies under development for early breast cancer detection, and to scrutinize the process of medical technology development, adoption, and dissemination. The committee is gathering information on these topics for its report in a number of ways, including two public workshops that bring in outside expertise. The first workshop on \

Strategies to Protect the Health of Deployed U.S. Forces: Analytical Framework for Assessing Risks - National Research Council (The National Academies Press, 2000)
Deployment of forces in hostile or unfamiliar environments is inherently risky. The changing missions and increasing use of U.S. forces around the globe in operations other than battle call for greater attention to threats of non-battle-related health problems2014including infections, pathogen- and vector-borne diseases, exposure to toxicants, and psychological and physical stress2014all of which must be avoided or treated differently from battle casualties. The likelihood of exposure to chemical and biological weapons adds to the array of tactical threats against which protection is required. The health consequences of physical and psychological stress, by themselves or through interaction with other threats, are also increasingly recognized. In addition, the military's responsibility in examining potential health and safety risks to its troops is increasing, and the spectrum of health concerns is broadening, from acute illness and injury due to pathogens and accidents to possible influences of low-level chemical exposures, which can manifest themselves in reproductive health and chronic illnesses years later, perhaps even after cessation of military service. Strategies to Protect the Health of Deployed U.S. Forces develops an analytical framework for assessing risks, which would encompass the risks of adversed health effects from battle injuries, including those from chemical- and biological-warfare agents, and non-battle-related health problems. The presumed spectrum of deployment ranged from peacekeeping to full-scale conflict.

The Aging Mind: Opportunities in Cognitive Research - National Research Council (The National Academies Press, 2000)
Possible new breakthroughs in understanding the aging mind that can be used to benefit older people are now emerging from research. This volume identifies the key scientific advances and the opportunities they bring. For example, science has learned that among older adults who do not suffer from Alzheimer's disease or other dementias, cognitive decline may depend less on loss of brain cells than on changes in the health of neurons and neural networks. Research on the processes that maintain neural health shows promise of revealing new ways to promote cognitive functioning in older people. Research is also showing how cognitive functioning depends on the conjunction of biology and culture. The ways older people adapt to changes in their nervous systems, and perhaps the changes themselves, are shaped by past life experiences, present living situations, changing motives, cultural expectations, and emerging technology, as well as by their physical health status and sensory-motor capabilities. Improved understanding of how physical and contextual factors interact can help explain why some cognitive functions are impaired in aging while others are spared and why cognitive capability is impaired in some older adults and spared in others. On the basis of these exciting findings, the report makes specific recommends that the U.S. government support three major new initiatives as the next steps for research.

Networking Health: Prescriptions for the Internet - National Research Council (The National Academies Press, 2000)
Consumer health websites have garnered considerable media attention, but only begin to scratch the surface of the more pervasive transformations the Internet could bring to health and health care. Networking Health examines ways in which the Internet may become a routine part of health care delivery and payment, public health, health education, and biomedical research. Building upon a series of site visits, this book: Weighs the role of the Internet versus private networks in uses ranging from the transfer of medical images to providing video-based medical consultations at a distance. Reviews technical challenges in the areas of quality of service, security, reliability, and access, and looks at the potential utility of the next generation of online technologies. Discusses ways health care organizations can use the Internet to support their strategic interests and explores barriers to a broader deployment of the Internet. Recommends steps that private and public sector entities can take to enhance the capabilities of the Internet for health purposes and to prepare health care organizations to adopt new Internet-based applications.

Informing the Future: Critical Issues in Health - Institute of Medicine (The National Academies Press, 2000)

Enhancing Data Systems to Improve the Quality of Cancer Care - Institute of Medicine; National Research Council (The National Academies Press, 2000)
One of the barriers to improving the quality of cancer care in the United States is the inadequacy of data systems. Out-of-date or incomplete information about the performance of doctors, hospitals, health plans, and public agencies makes it hard to gauge the quality of care. Augmenting today's data systems could start to fill the gap. This report examines the strengths and weaknesses of current systems and makes recommendations for enhancing data systems to improve the quality of cancer care. The board's recommendations fall into three key areas: Enhance key elements of the data system infrastructure (i.e., quality-of-care measures, cancer registries and databases, data collection technologies, and analytic capacity). Expand support for analyses of quality of cancer care using existing data systems. Monitor the effectiveness of data systems to promote quality improvement within health systems.

Managed Care Systems and Emerging Infections: Challenges and Opportunities for Strengthening Surveillance, Research, and Prevention: Workshop Summary - Institute of Medicine (The National Academies Press, 2000)
This workshop summary report examines how the managed care revolution has created both problems and opportunities in the fight against infectious diseases. It highlights ways in which managed care systems can aid research, develop clinical guidelines, manage the use of antibiotics, support public education efforts, and monitor the spread of emerging infections and microbial resistance.

Information for Women About the Safety of Silicone Breast Implants - Institute of Medicine (The National Academies Press, 2000)
When the Institute of Medicine began their comprehensive study of the safety of silicone breast implants, they heard directly from many women who suffer severe systemic illnesses. While convinced that in most instances the implants were not causally related to their conditions, the committee noted that many women felt strongly that they were not provided with adequate information on which to base their decision to have these implants. This short, 16-page guide puts this vital information in simple terms for women who have had implants or are considering them. Learn the risks2014and the facts2014today.

To Err Is Human: Building a Safer Health System - Institute of Medicine
Experts estimate that as many as 98,000 people die in any given year from medical errors that occur in hospitals. That's more than die from motor vehicle accidents, breast cancer, or AIDS2014three causes that receive far more public attention. Indeed, more people die annually from medication errors than from workplace injuries. Add the financial cost to the human tragedy, and medical error easily rises to the top ranks of urgent, widespread public problems. To Err Is Human breaks the silence that has surrounded medical errors and their consequence2014but not by pointing fingers at caring health care professionals who make honest mistakes. After all, to err is human. Instead, this book sets forth a national agenda2014with state and local implications2014for reducing medical errors and improving patient safety through the design of a safer health system. This volume reveals the often startling statistics of medical error and the disparity between the incidence of error and public perception of it, given many patients' expectations that the medical profession always performs perfectly. A careful examination is made of how the surrounding forces of legislation, regulation, and market activity influence the quality of care provided by health care organizations and then looks at their handling of medical mistakes. Using a detailed case study, the book reviews the current understanding of why these mistakes happen. A key theme is that legitimate liability concerns discourage reporting of errors2014which begs the question, \

Description and Analysis of the VA National Formulary - Institute of Medicine (The National Academies Press, 2000)
The VA National Formulary generated controversy, which motivated congressional scrutiny and a directive to the VA to commission this report reviewing the experience with the National Formulary and formulary system. This Institute of Medicine committee was pleased to assist the Congress with this review, in part because the committee saw in the VHA example an opportunity to understand and anticipate problems that all publicly funded programs are likely to encounter in this new age of pharmaceuticals. The Congress asked the committee to review the restrictiveness of the National Formulary, its impact on the costs and quality of care in the VHA, and how it compared to formularies and drug management practices in the private sector and in other public programs, especially Medicaid. Detailed in the pages that follow, the committee's findings and conclusions on these questions are, the committee believes, highly instructive, though not always in the ways that we anticipated.

Developing Technologies for Early Detection of Breast Cancer: Summary of Public Workshop #2 - Institute of Medicine; National Research Council (The National Academies Press, 2000)

Promoting Health: Intervention Strategies from Social and Behavioral Research - Institute of Medicine (The National Academies Press, 2000)
At the dawn of the twenty-first century, Americans enjoyed better overall health than at any other time in the nation's history. Rapid advancements in medical technologies, breakthroughs in understanding the genetic underpinnings of health and ill health, improvements in the effectiveness and variety of pharmaceuticals, and other developments in biomedical research have helped develop cures for many illnesses and improve the lives of those with chronic diseases. By itself, however, biomedical research cannot address the most significant challenges to improving public health. Approximately half of all causes of mortality in the United States are linked to social and behavioral factors such as smoking, diet, alcohol use, sedentary lifestyle, and accidents. Yet less than five percent of the money spent annually on U.S. health care is devoted to reducing the risks of these preventable conditions. Behavioral and social interventions offer great promise, but as yet their potential has been relatively poorly tapped. Promoting Health identifies those promising areas of social science and behavioral research that may address public health needs. It includes 12 papers2014commissioned from some of the nation's leading experts2014that review these issues in detail, and serves to assess whether the knowledge base of social and behavioral interventions has been useful, or could be useful, in the development of broader public health interventions.

Gulf War and Health: Volume 1: Depleted Uranium, Sarin, Pyridostigmine Bromide, and Vaccines - Institute of Medicine (The National Academies Press, 2000)
The men and women who served in the Gulf War theater were potentially exposed to a wide range of biological and chemical agents. Gulf War and Health: Volume 1 assesses the scientific literature concerning the association between these agents and the adverse health effects currently experienced by a large number of veterans.

Veterans and Agent Orange: Herbicide/Dioxin Exposure and Type 2 Diabetes - Institute of Medicine (The National Academies Press, 2000)
In response to the concerns voiced by Vietnam veterans and their families, Congress called upon the National Academy of Sciences (NAS) to review the scientific evidence on the possible health effects of exposure to Agent Orange and other herbicides. This call resulted in the creation of the first NAS Institute of Medicine Committee to Review the Health Effects in Vietnam Veterans of Exposure to Herbicides in 1992. The committee published its initial findings in the 1994 report Veterans and Agent Orange: Health Effects of Herbicides Used in Vietnam. This report is the result of a 1999 request from the Department of Veterans Affairs (DVA) under the aegis of the Veterans and Agent Orange research program. Specifically, DVA asked the committee to examine evidence regarding the association, if any, between Type 2 diabetes and exposure to dioxin and other chemical compounds in herbicides used in Vietnam. Veterans and Agent Orange: Herbicide\/Dioxin Exposure and Type 2 Diabetes reviews the scientific evidence regarding the association, if any, between Type 2 diabetes1 and exposure to dioxin2 and other chemical compounds in herbicides used in Vietnam. This report examines, to the extent that available data permitted meaningful determinations, (1) whether a statistical association with herbicide exposure exists, taking into account the strength of the scientific evidence and the appropriateness of the statistical and epidemiologic methods used to detect the association; (2) the increased risk of the disease among those exposed to herbicides during Vietnam service; and (3) whether there is a plausible biological mechanism or other evidence of a causal relationship between herbicide exposure and the disease.

Extending Medicare Reimbursement in Clinical Trials - Institute of Medicine
Increasingly over the past five years, uncertainty about reimbursement for routine patient care has been suspected as contributing to problems enrolling people in clinical trials. Clinical trial investigators cannot guarantee that Medicare will pay for the care required, and they must disclose this uncertainty to potential participants during the informed consent process. Since Medicare does not routinely \

Medicare Laboratory Payment Policy: Now and in the Future - Institute of Medicine (The National Academies Press, 2000)
Clinical laboratory tests play an integral role in helping physicians diagnose and treat patients. New developments in laboratory technology offer the prospect of improvements in diagnosis and care, but will place an increased burden on the payment system. Medicare, the federal program providing coverage of health-care services for the elderly and disabled, is the largest payer of clinical laboratory services. Originally designed in the early 1980s, Medicare's payment policy methodology for outpatient laboratory services has not evolved to take into account technology, market, and regulatory changes, and is now outdated. This report examines the current Medicare payment methodology for outpatient clinical laboratory services in the context of environmental and technological trends, evaluates payment policy alternatives, and makes recommendations to improve the system.